Discrete Dynamical Systems: A Brief Survey - Fernandes, Sara; Ramos, Carlos; Thapa, Gyan Bahadur; Lopes, Luís; Grácio, Clara (Journal of the Institute of Engineering, 2018)
Dynamical system is a mathematical formalization for any fixed rule that is described in time dependent fashion. The time can be measured by either of the number systems - integers, real numbers, complex numbers. A discrete dynamical system is a dynamical system whose state evolves over a state space in discrete time steps according to a fixed rule. This brief survey paper is concerned with the part of the work done by José Sousa Ramos [2] and some of his research students. We present the general theory of discrete dynamical systems and present results from applications to geometry, graph theory and synchronization. Journal of the Institute of Engineering, 2018, 14(1): 35-51